Komunikasi Dakwah Persuasif KH. Husaini Hanafi dalam Menanamkan Nilai-Nilai Islam Melalui Majelis Taklim Nafahattur Rabbani Kota Balikpapan - Hairul Hatami; Nahed Nuwairah; Najla Amaly (Al-Hiwar Jurnal Ilmu dan Teknik Dakwah, 2023)
Da'wah communication is an aspect of Muslim life which is one of the religious obligations and also has a goal to bring about changes in behavior, attitudes or actions that are in accordance with Islamic messages. Dai is not only to understand Islamic values ​​but also to try to direct Mad’u to always apply Islamic values ​​in his life so that changes are felt not only in understanding but also in Mad’u's attitudes, behavior and actions. To achieve this goal, an appropriate persuasive communication strategy is needed in carrying out da'wah activities so that the messages of Islamic teachings (messages) reach the mad’u through various means, one of which is through the Nafahattur Rabbani Taklim Council in Balikpapan City. The purpose of this research is to determine the persuasive da'wah communication carried out by KH. Husaini Hanafi in instilling Islamic values. This research method uses a qualitative descriptive method with the type of field research. Data collection was carried out by means of observation, interviews and documentation. Data analysis techniques by means of data reduction, data presentation and drawing conclusions. The research results show that the persuasive da'wah communication strategy implemented by KH. Husaini Hanafi in instilling Islamic values ​​through the Nafahattur Rabbani Taklim Council uses a family approach, uses stages of understanding mad’u, determines relevant messages and materials, starts da'wah communication by building a warm and comfortable situation and uses persuasive communication with participation methods, methods association, icing device method, and pay-off method.